FRI0275 Long-Term Survival and Baseline Prognostic Factors in a Wide Series of Patients with AAV from Spain. Usefulness of Prognostic Scores (Revas Study). (9th June 2015) - Solans-Laqué, R.; Rodriguez-Carballeira, M.; Fraile, G.; Castillo, M.J.; Rios, J.; Saez, L.; Solanich, X.; Caminal, L.; Oristrell, J.; Pasquau, F.; Fonseca, E.; Calleja, J.; et al.
Abstract : Background: AAV are still related to a high morbidity and mortality in spite of therapeutic advances.To identify factors present at diagnosis that are associated with a worse prognosis, it is essential to tailoring the treatment Objectives: To describe the long-term survival rate and possible prognostic factors at presentation in a large cohort of patients with AAV from Spain, and compare BVAS a FFS prognostic scores Methods: Multicenter retrospective-longitudinal study that included patients diagnosed with AAV between Jan1995 and Dec 2013 in 20 Hospitals from Spain (REVAS Study). Statistical analysis was done using SPSS vs19. Results: Four hundred and fifty patients (50.4% men) were included: 184 GPA, 167 MPA and 99 EGPA. ANCA were positive in 86.4% of cases:36.2% C-ANCA, 50.2% P-ANCA. Mean age at diagnosis was 55.6±17.4 y. Mean time to diagnosis was 4 weeks (0-240). The most frequent symptoms at diagnosis were fever (53%), constitutional symptoms (51%), arthralgia (53%), hypertension (29%), purpura (20%) and hemoptisis (19%). Renal failure was present in 47% of cases, lung involvement in 45.3%, pulmonary-renal syndrome in 16%, and cardiac involvement in 11%. Sensory peripheral neuropathy was detected in 16% of cases, mononeuritis multiplex in 28% and CVA in 4.5%. ENT was observed in 35% and eye involvement in 20%. All patients received oral glucocorticoids. Cyclophosphamide was given to 286 patients (45.3%IV and 38% oral). Dialysis was required in 19% of cases and plasma exchange in 7%. During the follow-up 40% of patients suffered bacterial infections, 10% sepsis 14.6% opportunistic infections and 6% neoplasms. One hundred and twenty-nine (28.7%) died: 74 (44.3%) with MPA, 41 (22.3%) with WG and 14 (14%) with CSS. Mean survival was 82.5 months (0-307). Mortality was significantly higher in MPA (p=0.00). Poor prognosis factors at diagnosis were renal failure (HR 1.6), cardiac failure (HR 3.3), bacterial infections (HR 1.8)and age at diagnosis >65y (HR 4.1).BVAS and FFS were significantly associated with outcome. Conclusions: Among AAV, PAM is associated with the worse prognosis. Renal and cardiac failure, bacterial infections, and age at diagnosis >65y, are associated with a poor clinical outcome. Three of these factors are included in the revised version of FFS, supporting its usefulness as a prognostic score. References: Flossmann O, Berden A, de Groot K et al. Long-term patient survival in ANCA-associated vasculitis. ARD 2011;70:488–94. Guillevin L, C, Seror R, et al.The Five-Factor Score Revisited Assessment of Prognoses of Systemic Necrotizing Vasculitides. Medicine 2011;90:19-27. Disclosure of Interest: None declared